Clinal variation in the morph ratio of Black Sparrowhawks Accipiter melanoleucus in South Africa and its correlation with environmental variables. (8th May 2014) - Amar, Arjun; Koeslag, Ann; Malan, Gerard; Brown, Mark; Wreford, Erin; Arroyo, Beatriz
<x xml:space="preserve">Abstract</x> The morph ratio distribution in polymorphic species often varies clinally, with a gradual change in morph ratios across the distributional range of the species. In polymorphic bird populations, clinal variation is rarely quantified. We describe a cline in the morph ratios of Black Sparrowhawks across South Africa, which is principally driven by a higher ratio of dark morph birds in the newly colonized southwest of the country. Across the 1400 km of our cline, the probability of a bird being a dark morph declined from over 80% close to the Cape Peninsula to under 20% in the northeast. Higher frequencies of dark morphs were associated with a higher proportion of rainfall falling during the winter breeding months. Further investigation revealed relationships between the proportion of dark morphs and altitude, amount of rainfall during the breeding months, and an interaction between this variable and temperature. These results provide some support for the suggestion that the higher frequency of dark morphs in the southwest is an adaptive response, rather than the result of a founder effect or genetic drift. These findings also suggest that, in theory, polymorphic species may be better adapted to cope with the challenges of climate change or may be able to expand their ranges more quickly into novel climatic areas, since selection pressure can act on a pre‐existing trait that may be beneficial in new conditions.